PHORNOGRAPHIC ADDICTIVE IN ADOLESCENTS AT SMKN 1 SOUTH CIKARANG YEAR 2021 - Musmundiroh Musmundiroh (Indonesian Journal for Health Sciences, 2022)
Addiction to pornography leads to negative consequences for children's behavior and brain damage beyond drug-induced damage. Teenagers who are exposed to pornography addiction cause deviant behavior to have sex before married, make out, masturbate, his study aims to find out what factors that   influence pornography addiction in adolescents at SMK Negeri 1 Cikarang Selatan in 2021. The research method used quantitative with cross sectional study approach. The data collection techniques in this study use the instrument by questionnaire. Univariate results show that the highest percentage are respondents with pornographic addiction behavior in adolescents as much as 74% of adolescents experiencing pornography addiction. The results of the bivariate selection above, obtained Independent variables that can proceed to the multivariate modeling stage, namely the variables: Attitude, Use of software, Peers and Gender.  In the multivariate modeling stage, peer and gender variables were re-entered into the model, apparently there were no more peer and gender variables. From the multivariate analysis, it turns out that the variables that are significantly related to pornography addiction are the attitude variable and the use of software.  another variable (peers and gender) whose p value is 0.05 The most dominant software use variable is related to pornography addiction